Composition and Transformation of Dissolved Organic Matter in the Baltic Sea - Seidel, Michael; Manecki, Marcus; Herlemann, Daniel P. R.; Deutsch, Barbara; Schulz-Bull, Detlef; Jürgens, Klaus; Dittmar, Thorsten (Frontiers in Earth Science, 2017)
The processing of terrestrial dissolved organic matter (DOM) in coastal shelf seas is an important part of the global carbon cycle, yet, it is still not well understood. One of the largest brackish shelf seas, the Baltic Sea in northern Europe, is characterized by high freshwater input from sub-arctic rivers and limited water exchange with the Atlantic Ocean via the North Sea. We studied the molecular and isotopic composition and turnover of solid-phase extractable (SPE) DOM and its transformation along the salinity and redox continuum of the Baltic Sea during spring and autumn. We applied ultrahigh-resolution mass spectrometry and other geochemical and biological approaches. Our data demonstrate a large influx of terrestrial riverine DOM, especially into the northern part of the Baltic Sea. The DOM composition in the central Baltic Sea changed seasonally and was mainly related to autochthonous production by phytoplankton in spring. Especially in the northern, river-dominated basins, a major fraction of riverine DOM was removed, likely by bio- and photo-degradation. We estimate that the removal rate of terrestrial DOM in the Baltic Sea (Bothnian Bay to the Danish Straits/Kattegat area) is 1.6 – 1.9 Tg C per year which is 43 to 51% of the total riverine input. The export of terrestrial DOM from the Danish Straits/Kattegat area towards the North Sea is 1.8 – 2.1 Tg C per year. Due to the long residence time of terrestrial DOM in the Baltic Sea (total of ca. 12 years), seasonal variations caused by bio- and photo-transformations and riverine discharge are dampened, resulting in a relatively invariant DOM molecular and isotopic signature exported to the North Sea. In the deep stagnant basins of the Baltic Sea, the DOM composition and dissolved organic nitrogen concentrations changed seasonally, likely because of vertical particle transport and subsequent degradation releasing DOM. DOM in the deep anoxic basins was also enriched in sulfur-containing organic molecules, pointing to abiotic sulfurization of DOM under sulfidic conditions.